Health disparities among older women in India during the COVID-19 pandemic - Aditi Tomar; Md Mahbub Hossain (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - Older women in India continually experience disparities in health. The legally enforced lockdown in India has impacted both physical and psychosocial well-being of the populace. Amid the restrictions on mobility during the lockdown, older adults are presented with challenges such as impaired access to healthcare services, nonavailability of attendants and prolonged social isolation. Due to these challenges, disparities related to gender and age may considerably widen. The potential health threats may particularly afflict older women, who bear a disproportionate threat to illnesses, compared to their male counterparts. Design/methodology/approach - This commentary explores how health threats among older Indian women may have worsened during the lockdown. The authors also propose recommendations for expanding health and social care to older women in India. Findings - Approaches aimed at strengthening gerontological social work must be duly adopted, especially during the ongoing pandemic. Public institutions and development partners should utilize and if needed, overhaul existing resources and policies to adequately serve this marginalized group. Older women, especially those residing in unbearable circumstances, should be identified and brought under comprehensive care coverage within the social landscape. Originality/value - This article proposes recommendations to foster gerontological social work among older Indian women.